Oxygen switches: Refueling for cancer radiotherapy - Li, Xianghui; Wang, Haoran; Li, Zhiyan; Tao, Feng; Wu, Jinhui; Guan, Wenxian; Liu, Song (Frontiers in Oncology, 2023)
Radiotherapy remains as the major therapeutic intervention for tumor patients. However, the hypoxic tumor microenvironment leads to the treatment resistance. Recently, a burgeoning number of nano radiosensitizer that designed for increase the oxygen concentration in tumor were reported. These nano radiosensitizers served as oxygen carriers, oxygen generators, and even sustained oxygen pumps, attracting increased research interest. In this review, we focus on the novel oxygen-enrich nano radiosensitizers, which we call them oxygen switches, and highlight their influence in radiotherapy through different strategies. Physical strategies-based oxygen switches carried O2 into tumor via their high oxygen capacity. The chemical reactions to generate O2 in situ were triggered by chemical strategies-based oxygen switches. Biological strategies-based oxygen switches regulated tumor metabolism, remodeled tumor vasculature, and even introduced microorganisms-mediated photosynthesis for long-lasting hypoxia alleviating. Moreover, the challenges and perspectives of oxygen switches-mediated oxygen-enrich radiotherapy were discussed.